2018
DOI: 10.1590/s1980-6574201700si0088
|View full text |Cite
|
Sign up to set email alerts
|

Individual and average responses of sleep quality and daytime sleepiness after four weeks of strength training in adolescents

Abstract: to 68.4% and from 52.6% to 31.6%, respectively. The comparisons of high and low responders to exercise training show that adolescents who reduced ≥3 points in the score of a least one sleep parameter presented lower weight, fat mass, and fat percentage (p<0.05). Conclusion: A short-term strength-training program is able to improve global sleep quality, but not daytime sleepiness in adolescents. Furthermore, the changes after training are highly heterogeneous. Further studies are required to better understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…It is interesting to note that the time of training seems to be important to promote this effect. For instance, Lira et al (22) found no changes in ESS score (10.3 ± 3.3 vs. 8.8 ± 4.0; p = 0.131) after a 4-week protocol of ST. Thus, it is possible that these differences may be attributed exclusively to the duration of the program.…”
Section: Discussionmentioning
confidence: 97%
“…It is interesting to note that the time of training seems to be important to promote this effect. For instance, Lira et al (22) found no changes in ESS score (10.3 ± 3.3 vs. 8.8 ± 4.0; p = 0.131) after a 4-week protocol of ST. Thus, it is possible that these differences may be attributed exclusively to the duration of the program.…”
Section: Discussionmentioning
confidence: 97%
“…Por ser um processo fisiológico, o sono está envolvido em diversos aspectos comportamentais como a hiperatividade, o humor e a agressividade, além de contribuir com funções cognitivas em crianças e adolescentes (Engle-Friedman et al, 2003;Zuculo et al, 2014). Durante a adolescência, o sono se torna ainda mais importante já que o indivíduo experimenta diversas transformações comuns a esta fase da vida (Lyra et al, 2017), além disso, sofre modificações, desenvolvendo características próprias e passando pela influência de hábitos de vida que geram perturbação em seu ciclo (Pinto, Pinto, Rebelo-Pinto & Paiva 2016).…”
Section: Discussionunclassified